Upaya BPJS Kesehatan Kantor Cabang Palangka Raya dalam Meningkatkan Pemahaman Peserta melalui Pelayanan dan Sosialisasi Program JKN - Clodia Cindy; Desha Delpia; Devi Winda Yanti; Dhina Sri Widyaningsih (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The National Health Insurance Program (JKN) administered by BPJS Kesehatan has achieved high membership coverage and is approaching Universal Health Coverage (UHC). However, there remain issues regarding participants' understanding of their rights, obligations, and service procedures, particularly in Palangka Raya City. This study aims to analyze the efforts of the BPJS Kesehatan Palangka Raya Branch Office in improving participants' understanding through JKN program services and socialization. The study employed a descriptive qualitative approach using interview, observation, and documentation techniques. The research findings indicate that some participants' do not yet understand the membership mechanisms, such as administration, contribution payments, health facility changes, and the arrears rehabilitation program. Direct services were considered more effective in improving participants' understanding because interaction with officers facilitates information delivery. Meanwhile, socialization serves as a preventive measure. Thus, services and socialization complement each other in improving participants' understanding.